History and background of kidney transplantation in Uzbekistan - Z. T. Matkarimov; F. S. Bahritdinov; R. A. Ibadov; A. S. Suyumov; Q. O. Mahmudov; A. R. Ahmedov; S. I. Shernazarov; M. O. Rustamov; Z. U. Abdugafurov; U. M. Saatova; J. B. Urinov (Вестник трансплантологии и искусственных органов, 2022)
This paper presents a brief outline of the history of transplantation service in the Republic of Uzbekistan, which originated at the country’s Center for Kidney Transplantation. The role played by outstanding scientists in Uzbekistan, their works and efforts towards the creation of a separate area of clinical and scientific medicine in Uzbekistan, are highlighted. Achievements by the research school of U.A. Aripov, Academician of the Academy of Sciences of the Republic of Uzbekistan, who performed the first successful kidney transplantation in 1972, are shown. The ups and downs of national transplantation nephrology, as well as the birth of a national school of kidney transplantation, domiciled at the Vakhidov Republican Specialized Scientific and Practical Medical Center of Surgery, headed by academician F.G. Nazirov, and giving a stimulus to the «second breath» of the national school of transplantology, is reflected. Separate attention is devoted to the actual problems of national transplantology, moral, ethical and regulatory issues that inevitably accompany this scientific and clinical direction are reflected. Kidney transplant outcomes in Uzbekistan are given, the prospects for further scientific and clinical directions are indicated.